Analyzing the impact of pulsatile flow on drug release from a single strut of a drug-eluting stent. (January 2023) - Abbasnezhad, N.; Shirinbayan, M.; Champmartin, S.; Bakir, F.
Abstract: In this study, in-vitro experiments were performed to investigate the drug release from a single strut of a drug-eluting stent with respect to the systolic-diastolic flow and the continuous flow. Regarding, a test bench comprising a single strut and agarose gel as an arterial wall model was designed. The model chosen represents a large-scaled strut of a stent, to limit the effect of the geometrical shape of the stents on the drug release results. The comparison is carried out between two continuous flow rates and a systolic-diastolic flow pattern varying between these two flow rates, with a frequency of 70 beats per minute. The stent model is a polylactic- co -glycolic acid film (50:50) loaded with 10 % diclofenac sodium. A compartment of agarose gel (1 %) and a phosphate-buffered saline solution at 37 °C are employed to mimic the arterial wall and the blood, respectively. Our results show the importance of flow type on the drug release from the stent and distribution of drug in the hydrogel, such that the pulsatility promotes an increase in the quantity of drug absorbed into the hydrogel.